Recent developments on exchange rates - Lardic, Sandrine (Palgrave Macmillan, 2004)
This collection examines recent developments in exchange rate analysis. In the first part, two exchange rate models are proposed: a model which combines heterogeneous agents and transaction costs, and a dynamic general-equilibrium two-country sticky-price model. The second part of the book deals with econometric aspects of the exchange rate dynamics linked to regime-switching and structural breaks. In the third part of the book, an analysis of speculative attacks and monetary policy is presented.